Rational Addiction and Time Consistency: An Empirical Test - Luca Piccoli; Silvia Tiezzi (Institute of Labor Economics (IZA), 2020)
This paper deals with one of the main empirical problems associated with the rational addiction theory, namely that its derived demand equation is not empirically distinguishable from models with forward looking behavior, but with time inconsistent preferences. The implication is that, even when forward looking behavior is supported by data, the standard rational addiction equation cannot distinguish between time consistency and inconsistency in preferences. We show that an encompassing general specification of the rational addiction model embeds the possibility of testing for time consistent versus time inconsistent naïve agents. We use a panel of Russian individuals to estimate a rational addiction equation for tobacco with time inconsistent preferences, where GMM estimators deal with errors in variables and unobserved heterogeneity. The results conform to the theoretical predictions and the proposed test for time consistency does not reject the hypothesis that Russian cigarettes consumers discount future utility exponentially. We further show that the proposed empirical specification of the Euler equation, whilst being indistinguishable from the general empirical specification of the rational addiction model, it allows to identify more structural parameters, such as an upper-bound for the parameter capturing present bias in time preferences.
Keywords: C23; D03; D12; 330; rational addiction; general versus standard specification; time consistency; naïveté; GMM